Relationship Between Body Image Perception, Eating Habits and Hemoglobin Levels among Adolescent Girls : A Cross-Sectional Study - Sabatina Windyaningrum; Dinda Oktia Maghfiroh; Naila Farihatul Itsnainy; Dellis Eka Mutiasari (Prodi D III Kebidanan Fakultas Ilmu Kesehatan Universitas Ibrahimy, 2026)
Adolescence is a critical period marked by rapid physical and psychological changes that contribute to the formation of body image, which may influence health-related behaviors such as dietary habits and nutritional status. This study aimed to examine the relationship between body image perception, dietary habits, and hemoglobin levels among adolescent girls. An analytical observational study with a cross-sectional design was conducted involving 70 tenth-grade female students at Public Vocational School 3 Malang. Body image was assessed using the Multidimensional Body-Self Relations Questionnaire–Appearance Scale (MBSRQ-AS), while dietary habits were evaluated using the Adolescent Food Habits Checklist (AFHC). Hemoglobin levels were measured using standard procedures. Pearson correlation analysis showed a significant relationship between body image perception and dietary habits (p = 0.046; r = 0.24), whereas no significant association was found between body image perception and hemoglobin levels (p = 0.983). These findings indicate that adolescent girls with a more positive body image tend to adopt healthier eating habits, although body image does not directly influence hemoglobin levels. The results suggest that school-based nutrition programs should incorporate body image education as part of adolescent health promotion to encourage healthy dietary behaviors, which may indirectly support optimal nutritional status.